Investment tax incentives and their big time-to-build fiscal multiplier - Dimitrios Bermperoglou; Yota Deli; Sarantis Kalyvitis (Kiel Institute for the World Economy (IfW), 2019)
This paper studies how investment tax incentives stimulate output in a medium-scale DSGE model, which allows for a variety of fiscal financing mechanisms. We find that the horizon following a positive shock in investment tax incentives is crucial. The shock is highly expansionary in the long run, with the relevant fiscal multiplier substantially exceeding 1, but this effect only becomes visible after two to three years. Our analysis indicates that a rise in the marginal product of labor and the demand for labor trigger this expansion, which is an effect that partial equilibrium studies ignore. The results suggest that investment tax incentives are even more effective when nominal wages adjust faster.
Keywords: E32; E62; H29; 330; private investment incentives; investment tax credit; fiscal multipliers